2017
DOI: 10.1111/his.13324
|View full text |Cite
|
Sign up to set email alerts
|

The histopathological classification, diagnosis and differential diagnosis of mucinous appendiceal neoplasms, appendiceal adenocarcinomas and pseudomyxoma peritonei

Abstract: The vermiform appendix is the primary site of several distinctive benign and malignant neoplasms. Some can produce the clinical syndrome of pseudomyxoma peritonei (PMP). A consensus on their terminology was reached by an international panel of pathologists and clinicians working under the auspices of the Peritoneal Surface Oncology Group International (PSOGI), and this review discusses the application of the PSOGI classification to routine reporting. We discuss diagnosis and differential diagnosis together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
222
0
26

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 242 publications
(253 citation statements)
references
References 69 publications
5
222
0
26
Order By: Relevance
“…Serrated pathology of the appendix is an enigmatic subject . It is relatively common, and this study has shown that it is sometimes coincident with ADD and complicated ADD.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Serrated pathology of the appendix is an enigmatic subject . It is relatively common, and this study has shown that it is sometimes coincident with ADD and complicated ADD.…”
Section: Discussionmentioning
confidence: 78%
“…Nevertheless, we accept that the coexistence of the two entities may provide a route by which the neoplastic epithelium and associated mucin of LAMNs may reach the peritoneal surface, despite their indolent appearance, via one or more diverticula, essentially bypassing the muscularis propria . As an extension of this process, pseudomyxoma peritonei associated with LAMN is usually the result of rupture of the cystic neoplasm and seeding of mucin and neoplastic epithelium into the peritoneal cavity, rather than direct invasion …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations